Selection criteria of strategic goals for local governments - Ignacy, Jarosław; Kopyściański, Tomasz (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2011)
Aim: Local development strategy is a widespread and commonly used instrument in public management. Strategies are applied by municipalities to develop their full potential. A key factor in effective use of strategies for local development are criteria for selecting strategic goals. The article is an attempt to provide applicable selection criteria recommended for local authorities for selection of strategic goals
Argumenta Oeconomica, 2011, Nr 2 (27), s. 15-36
Keywords: strategic management; strategic planning; strategic goals; municipality; local government management; local development strategy; local government